How Europe underdeveloped Africa - Rodney, Walter; Davis, Angela Y. (Angela Yvonne), 1944-; Harding, Vincent; Hill, Robert A., 1943-; Strickland, William, 1937-; Babu, Abdul Rahman Mohamed; Askews and Holts Library Services (London: New York: Verso, 2018)
The classic work of political, economic, and historical analysis, powerfully introduced by Angela Davis In his short life, the Guyanese intellectual Walter Rodney emerged as one of the leading thinkers and activists of the anticolonial revolution, leading movements in North America, South America, the African continent, and the Caribbean. In each locale, Rodney found himself a lightning rod for working class Black Power. His deportation catalyzed 20th century Jamaica's most significant rebellion, the 1968 Rodney riots, and his scholarship trained a generation how to think politics at an international scale. In 1980, shortly after founding of the Working People's Alliance in Guyana, the 38-year-old Rodney would be assassinated. In his magnum opus, How Europe Underdeveloped Africa , Rodney incisively argues that grasping "the great divergence" between the west and the rest can only be explained as the exploitation of the latter by the former. This meticulously researched analysis of the abiding repercussions of European colonialism on the continent of Africa has not only informed decades of scholarship and activism, it remains an indispensable study for grasping global inequality today.
Foreword / by Angela Y. Davis -- Preface -- Introduction / by Vincent Harding, Robert Hill, William Strickland -- Some questions on development -- How Africa developed before the coming of the Europeans -- up to the fifteenth century -- Africa's contribution to European capitalist development -- the pre-colonial period -- Europe and the roots of African underdevelopment -- to 1885 -- Africa's contributions to the capitalist development of Europe -- the colonial development -- Colonialism as a system for underdeveloping Africa -- Postscript / by A. M. Babu.
"First published in the UK by Bogle-L'Ouverture Publications 1972."
Includes bibliographical references and index.
Keywords: Colonial influence; Economic history; International economic relations; Africa -- Economic conditions; Africa -- Colonial influence; Europe -- Foreign economic relations -- Africa; Africa -- Foreign economic relations -- Europe; Africa; Europe